Inoculação de azospirillum brasilense e doses de nitrogênio em milho para produção de silagem e grãos - Skonieski, Fernando Reimann (2015)
This work has been developed in order to evaluate the effect of Azospirillum brasilense inoculation and nitrogen fertilization on the development of the maize crop for silage and grain. Experiments were conducted in the cities of Erechim, RS, in 2012/2013 and 2013/2014 harvests employing hybrid AS 1572 and Defender and at Santa Maria, in 2013/2014 harvest with AG 1572 and AG 9030 hybrids. Treatments followed randomized blocks design model in factorial arrangement composed by two maize hybrids, N fertilization levels (0, 60, 120, 240 and 480 kg/ha), inoculated or not with Azospirillum brasilense. Seeds were inoculated with Azospirillum brasilense Ab-V5 and Ab-V6 strains with 2.0 x 108 CFU/mL and 6.6 x 106 CFU/seed of concentration. Nitrogen fertilization was performed with 30 kg/ha dose, applied in the planting furrow, and the remaining fertilization was applied in coverage at growth stages. In the 2012/2013 harvest mineral N content (N-NO2 -/NO3 - e NNH3/ NH4 +) in the soil and total nitrogen in the plant were evaluated. Usually, ammoniacal nitrogen content (44.97 mg/kg soil) was higher than nitric nitrogen content (21.90 mg/kg soil). Insofar as the crop development advanced and wherein nitrogen doses were applied in coverage, the total mineral nitrogen in the soil increased. Increasing nitrogen doses in coverage mineral N content in the soil increased, the dose of 480 kg/ha nitrogen associated with inoculation of A. brasilense showed the highest mineral N in the soil. When maturation stage advanced, reduction of nitrogen concentration in the plant was observed, whereas the amount of N extraction in the soil increased. Interactions between inoculation with A. brasilense and harvests, among inoculation and N doses and between inoculation and maize hybrids defined silages yield. The increasing of N doses increased silage protein content, without modifying materials digestibility. Inoculation with A. brasilense increased silages organic matter digestibility at Santa Maria, RS, in addition to increasing the EE and TDN content and reduce the ADF silage at Erechim, RS. Concerning grain yield, interaction between nitrogen doses and inoculation with A. brasilense was perceived. Nitrogen doses between 60 and 120 kg/ha favored plants grain yield inoculated with A. brasilense at Erechim, RS. In Santa Maria, the interaction was favored at doses between 240 and 480 kg/ha. Inoculation with Azospirillum brasilense can be used as a strategy to promote increases in the yield of silage and grains, since interactions with hybrids, N doses and harvests are observed.